7(x-6)+2(x-7)=5(x-4)

Simple and best practice solution for 7(x-6)+2(x-7)=5(x-4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7(x-6)+2(x-7)=5(x-4) equation:


Simplifying
7(x + -6) + 2(x + -7) = 5(x + -4)

Reorder the terms:
7(-6 + x) + 2(x + -7) = 5(x + -4)
(-6 * 7 + x * 7) + 2(x + -7) = 5(x + -4)
(-42 + 7x) + 2(x + -7) = 5(x + -4)

Reorder the terms:
-42 + 7x + 2(-7 + x) = 5(x + -4)
-42 + 7x + (-7 * 2 + x * 2) = 5(x + -4)
-42 + 7x + (-14 + 2x) = 5(x + -4)

Reorder the terms:
-42 + -14 + 7x + 2x = 5(x + -4)

Combine like terms: -42 + -14 = -56
-56 + 7x + 2x = 5(x + -4)

Combine like terms: 7x + 2x = 9x
-56 + 9x = 5(x + -4)

Reorder the terms:
-56 + 9x = 5(-4 + x)
-56 + 9x = (-4 * 5 + x * 5)
-56 + 9x = (-20 + 5x)

Solving
-56 + 9x = -20 + 5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-5x' to each side of the equation.
-56 + 9x + -5x = -20 + 5x + -5x

Combine like terms: 9x + -5x = 4x
-56 + 4x = -20 + 5x + -5x

Combine like terms: 5x + -5x = 0
-56 + 4x = -20 + 0
-56 + 4x = -20

Add '56' to each side of the equation.
-56 + 56 + 4x = -20 + 56

Combine like terms: -56 + 56 = 0
0 + 4x = -20 + 56
4x = -20 + 56

Combine like terms: -20 + 56 = 36
4x = 36

Divide each side by '4'.
x = 9

Simplifying
x = 9

See similar equations:

| 450000.00-22000.00x=277000.00 | | 4x+16+2x=46 | | 2-7=45 | | 94-4x=14+20 | | 9x-16=2x+2 | | 4x+8=20-10x | | 14-10x=50-31x | | -8/20+15/20 | | 9x-15=2x+2 | | 10-8x=118-36x | | -155000.00-22000.00x=3 | | 6n-1=n+14 | | -142-10x=50-31x | | 5(x+4)-3(x-4)=3x+29 | | 0.3(2x-3)=0.2x+0.9 | | 2/5(8+3x)=16/5 | | 450000.00-22000.00=0 | | 9x+15=3x-15 | | -38-2x=3x+14 | | 91-5x=2x-14 | | 4(x-3)+3(x+7)=16 | | 61-4=9x+22 | | z-36=58 | | 2n^2+9n-23=3 | | 50x-20=3 | | -3/5x3x3x3 | | 2x-2-4=5 | | 3(1x+1/3)=26 | | 1.5(x+2)=7.5 | | 10(x+4)-3(2x+5)-1=10 | | 112-5x=10x-22 | | b+2a+4c=b |

Equations solver categories